Spartan Spasms 1927-11 (November 1927) - San Jose State College:::Creator::::::::::::; Taylor, Clarence G.:::Editor::::::::::::
Vol. 2, no. 1. This title was published as a college humor magazine with jokes, short stories, book reviews and current events. It was renamed Spartan Spasms after the first issue.